The Frequency of the Clinical Risk Factors in Postmenopausal Osteoporosis - Kutsal, Yesim Gokce; Savas, Serpil; Inanici, Fatma; Ozdemir, Oya; Karahan, Sevilay; Dogan, Asuman; Yazgan, Pelin (Turkish League Against Rheumatism, 2013)
Objectives: This study aims to identify the frequency of clinical risk factors associated with osteoporosis in postmenopausal women. Patients and methods: In this cross-sectional, observational, multicenter study, a total of 730 postmenopausal women were assessed for risk factors associated with osteoporosis. The assessment included a standardized questionnaire which recorded the following clinical risk factors: family and personal histories of fractures, prolonged immobilization, sun exposure, lifelong sedentary lifestyle, smoking history, low calcium intake in childhood and adulthood, excessive caffeine intake, high sodium intake, inadequate protein intake, number of pregnancies, age at menopause, the presence of premature menopause, primary and secondary amenorrhea, medical conditions, and chronic use of prescription drugs. Results: The most frequent clinical risk factors for osteoporosis were inadequate sun exposure (53.3%), current sedentary lifestyle (52.9%), low calcium intake in adulthood (45.1%) and childhood (41.9%), and sedentary lifestyle in adolescence (27.9%). A total of 707 patients (96.5%) described more than one risk factor, while 74.3% of the patients reported one clinical risk factor at least for secondary osteoporosis. Conclusion: Adequate sun exposure and proper intake of dietary calcium beginning in childhood combined with lifelong daily physical activity may play a role in preventing osteoporosis in postmenopausal women. In addition, physicians should be aware of the high probability of secondary osteoporosis in this patient group.
Postmenopozal osteoporozda klinik risk faktörlerinin si{dotless}kli{dotless}?i{dotless}
Keywords: Osteoporosis; postmenopausal; risk factor